Prototype Development of IoT Based Smart Waste Management System for Smart City. Issue 1 (July 2020) - Harith, Muhammad Zar Mohd Zaid; Hossain, Mohammad Asif; Ahmedy, Ismail; Idris, Mohd Yamani Idna; Soon, Tey Kok; Noor, Rafidah Md
Abstract: The inefficient waste collection system has resulted in environmental pollution and large consumption of sources of energy. This is because of inefficient waste collection systems result in smell pollution, unpleasant views, breading of insects, animal scavengers and rodents which also giving rise to a range of diseases when some waste bins are left overloaded and uncollected. As one of the efforts to overcome the inefficiency of the waste collection system problem and to achieve smart cities, an IoT (Internet of Things) based smart bin prototype is proposed in this paper. Altogether, it is an automatic centralized monitoring system that provides the timely status of a bin, enables optimal route planning for collections, reduces collection times, and saves costs as well as fuel consumption.